Tectorigenin Alleviates Inflammation, Apoptosis, and Ossification in Rat Tendon-Derived Stem Cells via Modulating NF-Kappa B and MAPK Pathways - Moqbel, Safwat Adel Abdo; Xu, Kai; Chen, Zhonggai; Xu, Langhai; He, Yuezhe; Wu, Zhipeng; Ma, Chiyuan; Ran, Jisheng; Wu, Lidong; Xiong, Yan (Frontiers in Cell and Developmental Biology, 2020)
Tendinopathy is a common musculoskeletal disorder, mainly affects the athletes and aged people. Tumor necrosis factor-α (TNF-α) plays an initiator role in tendinopathy. Tectorigenin is an extract component of Belam-canda Chinesis, which performs anti-inflammatory and anti-apoptosis effects. The present study stablished to investigate the role of tectorigenin against the pathogenetic effects of TNF-α on tendon-derived stem cells (TDSCs) in vivo and in vitro. The findings indicated that TNF-α is able to induce TDSC inflammation, apoptosis and ossification, as well as it is able to activate nuclear factor-kappa B and MAPK. Furthermore, the results confirmed that tectorigenin is able to inhibit the TNF-α-induced inflammation, apoptosis and ossification. Tectorigenin treatment decreases activation of NF-kappa B and MAPK signalling in TDSCs. In in vivo, tectorigenin ameliorates the tendinopathy in rat model. Thus, all these data reveal that tectorigenin has a potential treatment for tendinopathy